As relaç\~oes Brasil-África e o regime internacional de investimentos: Uma análise do ACFI do Brasil com Angola e Moçambique - Ana Saggioro Garcia; Gabriel Torres (Instituto de Pesquisa Econômica Aplicada (IPEA), 2021)
– This paper results from the project "Brazil's external agenda for Africa: evaluations and proposals", within which we analyze Brazil's performance in the international investment facilitation and protection regime, in order to take stock of the effects of the new Agreement of Cooperation and Investment Facilitation (ACFI) for Brazilian investments in Angola and Mozambique. We present the historical context of the emergence of bilateral investment treaties; the growing criticism of a political, economic and social nature about the effects of the treaties on public policies of the signatory countries, as well as the current context of reforms of the agreement models, in which the Brazilian ACFI is placed; the insertion of African countries in the international investment regime, with their domestic, bilateral and regional legislative framework to facilitate and protect foreign investment; and, finally, we provide an overview of public policies relevant to foreign investment in Angola and Mozambique, showing a comparative chart of the ACFI signed with Brazil and the other bilateral investment treaties in force in each of these countries.
Keywords: F53; F55; F59; F63; 330; foreign direct investment; bilateral investment treaties; Brazil; Africa